Akuntabilitas Pemerintah Desa Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Desa Siwalempu Kecamatan Sojol Kabupaten Donggala - Saputri, Ferda; Hattab, Syahruddin; Farista, Gita (JPS: Journal of Publicness Studies, 2025)
This study aims to describe and analyze the accountability of the village government in the management of the Village Revenue and Expenditure Budget (APBDesa) in Siwaleppu Village, Sojol District, Donggala Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The theory used is the theory of public accountability proposed by Malik Imron (2005), which consists of four main dimensions: accountability as a relationship, results-oriented accountability, accountability requires reporting, and accountability improves performance. The results of the study show that accountability in the management of the Regional Budget in Siwalempu Village has been implemented gradually and progressively. The village government has built a two-way relationship with the community through deliberative forums and public reporting, although the distribution of information is still uneven. Results-oriented accountability is reflected in the village government's focus on the tangible benefits of development activities, not just the preparation of administrative reports. In terms of reporting, even though it has been carried out regularly and formally through the Siskeudes system and annual reports, there are still obstacles in the accessibility and public understanding of the report. The application of accountability principles has also been proven to improve the performance of village governments, which is reflected in more orderly, transparent, and responsive public services. This study concludes that accountability is an important factor in realizing good village governance. Therefore, it is recommended that the village government increase information socialization, optimize village communication media, and strengthen the capacity of apparatus and supervisory institutions so that the governance of the Regional Budget is more transparent, participatory, and sustainable.